Actin-dependent mechanisms in AMPA receptor trafficking - Hanley, Jonathan G. (Frontiers in Cellular Neuroscience, 2014)
The precise regulation of AMPA receptor (AMPAR) number and subtype at the synapse is crucial for the regulation of excitatory neurotransmission, synaptic plasticity and the consequent formation of appropriate neural circuits during learning and memory. AMPAR trafficking involves the dynamic processes of exocytosis, endocytosis and endosomal recycling, all of which involve the actin cytoskeleton. The actin cytoskeleton is highly dynamic and highly regulated by an abundance of actin-binding proteins and upstream signalling pathways that modulate actin polymerization and depolymerisation. Actin dynamics generate forces that manipulate membranes in the process of vesicle biogenesis, and also for propelling vesicles through the cytoplasm to reach their destination. In addition, trafficking mechanisms exploit more stable aspects of the actin cytoskeleton by using actin-based motor proteins to traffic vesicular cargo along actin filaments. Numerous studies have shown that actin dynamics are critical for AMPAR localization and function. The identification of actin-binding proteins that physically interact with AMPAR subunits, and research into their mode of action is starting to shed light on the mechanisms involved. Such proteins either regulate actin dynamics to modulate mechanical forces exerted on AMPAR-containing membranes, or associate with actin filaments to target or transport AMPAR-containing vesicles to specific subcellular regions. In addition, actin-regulatory proteins that do not physically interact with AMPARs may influence AMPAR trafficking by regulating the local actin environment in the dendritic spine.